Performances Assessment of MOMA-Plus Method on Multiobjective Optimization Problems (European Journal of Pure and Applied Mathematics, 2020)
This work is devoted to evaluate the performances of the MOMA-plus method in solving multiobjective optimization problems. This assessment is doing on the complexity of its algorithm, the convergence and the diversity of solutions in relation to the Pareto front. All these parameters were evaluated on non-linear multiobjective test problems and obtained solutions are compared with those provided by the NSGA-II method. This comparative study made it possible tohighlight the performances of MOMA-plus method for solving non-linear multiobjective problems.
Keywords: Multiobjective optimization; MOMA-plus method; Performances assessment